Born local: two avenues to internationalization - Zoltán J. Ács; Siri Terjesen (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Are firms born Global? Because knowledge spillovers that lead to new venture creation are geographically constrained we believe that firms are born local. It follows that the decision to create sustainable new ventures is independent from the decision to interna-tionalize, even if that is the ultimate goal of the firm. We explore two avenues to interna-tionalize new ventures, a direct path described in much of the extant literature and an intermediated one. New ventures face high entry barriers and intellectual property rights protection to internationalization, which are circumvented by intermediating activities using existing multinational enterprises as facilitators of internationalization. However, new ventures using the intermediated mode of internationalization face transaction costs and rent extraction from multinational enterprises. Therefore, sustainable new ventures face a strategic decision on how to internationalize.
Keywords: L26; F23; M13; M16; 330; International Entrepreneurship; Multinational Enterprises; Knowledge Spillovers; Intermediated Internationalization; International New Ventures; Foreign Direct Investment; Unternehmer; Unternehmensgründung; Wissenstransfer; Multinationales Unternehmen; Region; Internationale Markteintrittsstrategie; Direktinvestition